2022
DOI: 10.30935/cedtech/12297
|View full text |Cite
|
Sign up to set email alerts
|

Gamification, Online Learning and Motivation: A Quantitative and Qualitative Analysis in Higher Education

Abstract: As a motivational teaching practice, gamification does not always work as expected. This paper supports these findings and adds the factor of online teaching analyzing the results of an experiment carried out in an online higher education context to test the relevance and motivational efficacy of ludic methodologies using learning and knowledge technology. Three groups of students (n=78, n=64, and n=74) participated in gamified experiences in the same subject. These groups were offered different approaches to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
0
9
0
1
Order By: Relevance
“…Both educational games, Kahoot and Quizizz, can be considered fairly lightweight uses of educational gamification. However, especially Kahoot is widely used and has shown various positive results in recent research [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both educational games, Kahoot and Quizizz, can be considered fairly lightweight uses of educational gamification. However, especially Kahoot is widely used and has shown various positive results in recent research [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nonetheless, this study's overall results align with previous research in Thailand [48], Turkey [49], and Iran [50] that highlighted positive impacts on learning outcomes. While many studies confirm the positive effects of these approaches [27,28], others indicate no significant differences in academic achievement and motivation between gamified and nongamified learning, emphasizing the importance of teacherstudent relationships and emotional factors in online teaching [42,43].…”
Section: Students' Learningmentioning
confidence: 99%
“…In contrast, Can and Dursun [42] found no significant differences in academic achievement and motivation between gamified and nongamified learning groups. Cespón and Lage [43] revealed that the use of technologies and gamification may not be as appealing as expected, with factors like teacher-student relationships, rewards, and alienation influencing student participation. The low participation rate emphasized the importance of considering both participating and nonparticipating students.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, gamification has been applied in various areas of teaching and learning English because of its great benefits. It was used to motivate learners and enhance their engagement in learning (Bal, 2019;Hanus & Fox, 2015;Jackson & McNamara, 2013;Mchucha et al, 2017;Torrado Cespón & Díaz Lage, 2022). In addition, gamified learning has been proven in some studies to have a positive influence on vocabulary learning (Katemba & Sinuhaji, 2021;Kijpoonphol & Phumchanin, 2018;Pham, 2022a;Waluyo & Brucol, 2021).…”
Section: Introductionmentioning
confidence: 99%